2016
DOI: 10.1186/s13048-016-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

p14 expression differences in ovarian benign, borderline and malignant epithelial tumors

Abstract: BackgroundAbnormalities in tumor suppressors p14, p16 and p53 are reported in several human cancers. In ovarian epithelial carcinogenesis, p16 and p53 show higher immunohistochemical staining frequencies in malignant tumors and are associated with poor prognoses. p14 was only analyzed in carcinomas, with conflicting results. There are no reports on its expression in benign and borderline tumors. This study aims to determine p14, p16 and p53 expression frequencies in ovarian benign, borderline and malignant tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There have been various biomarkers proposed to determine the malignant potential of borderline tumors, such as differential loss of p14 [ 66 ] in invasive tumors with respect to borderline, overexpression of interleukin 8 (IL-8) and its receptors [ 67 ], or multigenic signature to predict worse prognosis [ 68 ]; however, none of them have demonstrated high sensitivity rates.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various biomarkers proposed to determine the malignant potential of borderline tumors, such as differential loss of p14 [ 66 ] in invasive tumors with respect to borderline, overexpression of interleukin 8 (IL-8) and its receptors [ 67 ], or multigenic signature to predict worse prognosis [ 68 ]; however, none of them have demonstrated high sensitivity rates.…”
Section: Discussionmentioning
confidence: 99%
“…Snail protein expression in xenograft tumor was detected by immunohistochemistry and Western blot. According to the method, 6 immunohistochemical staining results were determined. Sinicrope modified method was determined to obtain the quantitative positive results.…”
Section: Pathologic Examination and Detection Of Snail Protein E-cadh...mentioning
confidence: 99%
“…Until recent years, investigators have identified another important regulator in this p53/MDM2 pathway, the cyclin-dependent kinase inhibitor p14 ARF (termed p19 ARF in the mouse) [17]. The p14 ARF protein is an alternative reading frame protein product of the CDKN2A/INK4A locus [18]. The other one is p16 INK4A protein [17].…”
Section: Introductionmentioning
confidence: 99%